Dung Beetles along a Tropical Altitudinal Gradient: Environmental Filtering on Taxonomic and Functional Diversity - Nunes, Cássio Alencar; Braga, Rodrigo Fagundes; Figueira, José Eugênio Cortes; Neves, Frederico de Siqueira; Fernandes, G. Wilson (PloS one, 2016)
Mountains provide an interesting context in which to study the many facets of biodiversity in response to macroclimate, since environmental conditions change rapidly due to elevation. Although the decrease in biodiversity with increasing elevation is generally accepted, our understanding of the variation of functional diversity along altitudinal gradients is still poorly known. The partitioning of diversity into spatial components can help to understand the processes that influence the distribution of species, and these studies are urgently needed in face of the increasing threats to mountain environments throughout the world. We describe the distribution of dung beetle diversity along an altitudinal gradient on a tropical mountain in southeastern Brazil, including the spatial partitioning of taxonomic and functional diversities. The altitudinal gradient ranged from 800 up to 1400 m a.s.l. and we collected dung beetles at every 100 m of altitude. We used the Rao Index to calculate γ, α and β diversity for taxonomic and functional diversity of dung beetles. Climatic, soil and vegetation variables were used to explain variation in community attributes along the altitudinal gradient. Dung beetle richness declined with altitude and was related to climatic and vegetation variables, but functional diversity did not follow the same pattern. Over 50% of γ taxonomic diversity was caused by among altitudes diversity (β), while almost 100% of functional diversity was due to the α component. Contrasting β taxonomic with β functional diversity, we suggest that there is ecological redundancy among communities and that the environment is filtering species in terms of the Grinnellian niche, rather than the Eltonian niche. β taxonomic diversity is caused mainly by the turnover component, reinforcing the hypothesis of environmental filtering. Global warming may have strong effects on mountain communities due to upslope range shifts and extinctions, and these events will lead to an even larger than previously expected loss of diversity as dung beetles γ taxonomic diversity is caused mainly by the β component.